Usability analysis of marker-based augmented reality application for the microcontroller study - Suhaili Beeran Kutty; Muhammad Azim Nazri; Che Nur Shafareen Afera Che Anuar; Murizah Kassim; Norakmar Arbain Sulaiman (Institute of Advanced Engineering and Science, 2024)
Virtual labs using augmented reality (AR) applications have brought transformation in teaching laboratory courses. However, in the field of engineering laboratories, the use of AR applications is still new. In this work, a marker-based AR application is used as a tool that enables a hands-on learning experience of microcontroller study. The software used to develop this application are Unity3D and Vuforia. C# programming language has also been used to provide the command for the interaction between the interface and the application. After the development of the application was complete, it was tested by a group of electrical engineering students. Then, the students are required to fill out a survey on the system usability scale (SUS) test. The SUS score of this application is 62.5. It was found that the perceived usability of the evaluated AR application as a teaching tool for laboratory courses is acceptable. This response shows the marker-based AR application has the potential to be used as a teaching aid in engineering laboratory courses.